2022
DOI: 10.3390/molecules27103066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ziziphus and Cordia Gums on Dough Properties and Baking Performance of Cookies

Abstract: The influence of 2% and 5% Cordia (CG) and Ziziphus (ZG) gums on dough characteristics and cookie quality was investigated. Micro-DoughLab, a texture analyzer (TA), a rapid viscoanalyzer (RVA), and solvent retention capacity were used to examine the effect of CG and ZG gums on dough physicochemical parameters (SRC) and cookie quality. The diameter, thickness, spread, and sensory evaluation of cookies were evaluated. With the addition of CG and ZG, dough softness, mixing time, and mixing tolerance index (MTI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…Alamri et al [ 24 ] suggested that the reduction in FV might be correlated with the lower amount of the total starch percentage in the blend due to the replacement with the gums. In line with our study, the reduction in the FV is also in line with the literature report in which ziziphus gum and Arabic gum lowered the viscosity of the wheat flour and starches [ 6 , 22 , 25 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Alamri et al [ 24 ] suggested that the reduction in FV might be correlated with the lower amount of the total starch percentage in the blend due to the replacement with the gums. In line with our study, the reduction in the FV is also in line with the literature report in which ziziphus gum and Arabic gum lowered the viscosity of the wheat flour and starches [ 6 , 22 , 25 ].…”
Section: Resultssupporting
confidence: 93%
“…Thus, gum addition negatively impacted the overall quality and acceptability of the cookies; hence, 3% acacia gum was a suitable level for cookie manufacturing. In line with the current findings, Mohamed, Alamri, Hussain, Ibraheem, Qasem, Shamlan, and Ababtain [ 6 ] also found that the cookies prepared with wheat flour with the addition of ziziphus gum and cordia gum remained less acceptable than the cookies prepared using only wheat flour. Conversely, the addition of prickly pear peel powder in the cookies at 20% and 30% improved the overall acceptability score of the cookies compared to the cookies without the powder [ 37 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Again, compared to bread flour, soft wheat flour (cake flour) was less influenced by MD or ZG gum because adding MD or ZG decreased the WRC, whereas adding MD and ZG to bread flour raised the WRC. The WRC of bread flour was boosted by other gums like cordia (Mohamed et al, 2022b). The effect of SuSRC showed no significant difference between the control and the blends, but a drop in SuSRC of the blends was lower than the control.…”
Section: Solvent Retention Capacity (Src)mentioning
confidence: 92%